High cadmium uptake ability of Bacillus cereus strains isolated from rhizosphere of Tagetes minuta L. growing in cadmium-polluted soil - Akhter, Kulsoom; Ghous, Tahseen; Awan, Muhammad Siddique; Ul-Abdin, Zain; Hussain, Basharat (Bangladesh Journal of Botany, 2018)
Microbes resistant to heavy metals develop mechanisms to accumulate Cd(II) in their cells. Two bacterial strains, Bacillus cereus AVP12 and B. cereus NC7401 which grew at high Cd(II) concentration were isolated from roots of Tagetes minuta L. growing in Cd(II) contaminated and uncontaminated soil. Minimum inhibitory concentration (MIC) and percent removal capacity were determined as function of pH, contact time and initial Cd(II) concentration. Bioaccumulation capacity was determined to observe possible effect of two different rhizospheres on Cd(II) removal capacity of both strains. Both strains were resistant up to 300 mg/l Cd(II) concentration. The percent removal capacity of both strains was maximum at pH 7 and incubation time of 24 hrs. High bioaccumulation capacity was observed with increasing Cd(II) concentration. Both Langmuir and Freundlich models fitted well to data of Cd(II) bioaccumulation. Though, maximum adsorption capacity (Qo) was observed for strains isolated from both types of rhizospheres, however remarkable Qo values of 434.0 and 212.7 mg/g were observed for Bacillus cereus AVP12 and NC7401, respectively isolated from polluted rhizosphere. Bacillus cereus strains growing in polluted rhizosphere can develop high Cd(II) uptake ability in comparison to non-polluted rhizosphere.